1997
DOI: 10.1046/j.1471-4159.1997.68062371.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Flupirtine on β‐Amyloid‐Induced Apoptosis in Neuronal Cells In Vitro: Prevention of Amyloid‐Induced Glutathione Depletion

Abstract: Effective drugs are not available to protect against ß-amyloid peptide (Aß)-induced neurotoxicity. Cortical neurons from rat embryos were treated with the toxic fragment Aß25-35 at 1 p~Min the presence or absence of flupirtine, a triaminopyridine, successfully applied clinically as a nonopiate analgesic drug. Five days later 1 ‚uM Aß25-35 caused reduction of cell viability to 31.1%. Preincubation of cells with flupirtine (1 or 5~ig/ ml) resulted in a significant increase of the percentage of viable cells (74.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…As illustrated in Figure 1b, a 24-h treatment of cortical cells with 25 mM Ab [25][26][27][28][29][30][31][32][33][34][35] increased the percentage of apoptotic cells, as assessed by 4 0 ,6-diamidino-2-phenylindole (DAPI) staining. This proapoptotic effect of Ab was totally suppressed by a 48-h pretreatment of the cells with the 12-LOX antisense oligonucleotide, whereas the sense or the scramble 12-LOX oligonucleotide did not show any protective action (Figure 1b).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As illustrated in Figure 1b, a 24-h treatment of cortical cells with 25 mM Ab [25][26][27][28][29][30][31][32][33][34][35] increased the percentage of apoptotic cells, as assessed by 4 0 ,6-diamidino-2-phenylindole (DAPI) staining. This proapoptotic effect of Ab was totally suppressed by a 48-h pretreatment of the cells with the 12-LOX antisense oligonucleotide, whereas the sense or the scramble 12-LOX oligonucleotide did not show any protective action (Figure 1b).…”
Section: Resultsmentioning
confidence: 89%
“…23 Alteration of glutathione metabolism is one of the events triggered by Ab 29 and was reported to occur in AD, 30 which suggested that this LOX might also participate in Ab-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of ceramide during A␤-induced neuronal cell death is instrumental as for its blockade by n-SMase antisense oligonucleotides, pharmacological n-SMase inhibitors or antioxidants such as the glutathione (GSH) precursor NAC, diphenyl iodonium can hinder the cytotoxic effect of A␤-peptides (Jana and Pahan, 2004;Lee et al, 2004;. It has been hypothesized that the decrease in GSH level observed after A␤ exposure (Mü ller et al, 1997;Pereira et al, 1999) could activate n-SMase, therefore leading to ceramide production (Lee et al, 2004). In this study, we establish that not only is the proapoptotic ceramide produced during A␤-induced neuronal cell death, but also the levels of the prosurvival S1P are diminished as a result of SphK1 down-regulation, thus tilting the ceramide/S1P biostat toward ceramide, as previously observed in tumor cells after anticancer treatments (Nava et al, 2000;Taha et al, 2004;Pchejetski et al, 2005;Bonhoure et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…2,3) However, other investigators have demonstrated that bamyloid (25-35) induces a depletion of neuronal glutathione (GSH) in neuronal culture. 4,5) In addition, both bA25-35 and bA1-42 Ca 2ϩ -dependently depleted endogenous glutathione in hippocampal astrocytes and secondarily depleted glutathione in neuronal cells. 5) Akama and his colleagues have demonstrated that the b-amyloid protein stimulates nitric oxide (NO) production in astrocytes by a cytokine-dependent pathway.…”
mentioning
confidence: 94%